Long-term cardiovascular health in adult cancer survivors. (November 2017) - Naaktgeboren, W.R.; Linschoten, M.; de Graeff, A.; v Rhenen, A.; Cramer, M.J.; Asselbergs, F.W.; Maas, A.H.E.M.; Teske, A.J.
Highlights: Cancer treatment can have long-term detrimental cardiovascular side-effects. Awareness of these long-term side-effects is of crucial value in the management of these patients. Prospective information is needed to fill the current gaps in knowledge (in particular regarding the long-term side-effects of non-anthracyclines). Multidisciplinary efforts will reduce the impact of the side-effects of anticancer treatments. Abstract: The number of cancer survivors has tremendously increased over the past decades as a result of aging of the population and improvements in early cancer detection and treatment. Ongoing successes in cancer treatment are expected to result in a further increase in the number of long-term survivors. However, cancer treatment can have detrimental cardiovascular side-effects that impact morbidity and mortality, reducing quality of life in cancer survivors. The spectrum of radiotherapy- and chemotherapy-induced cardiovascular disease is broad, varying from subclinical valvular dysfunction to overt congestive heart failure, and such effects may not be apparent for more than twenty years after the initial cancer treatment. Awareness of these long-term side-effects is of crucial value in the management of these patients, in order to reduce the impact of cardiovascular morbidity and mortality. This review provides a comprehensive overview of the long-term cardiovascular complications of cancer treatments (radiotherapy and chemotherapy) in adult cancer survivors.